Leveraging Generative AI in ELT: Teachers’ Integration Strategies and Pedagogical Adaptations - Dewi, Finita (JOLLT Journal of Languages and Language Teaching, 2025)
This study investigates how English teachers integrate Generative AI ChatGPT, Diffit, and Brisk into their instructional practices, focusing on their strategies, challenges and pedagogical adaptations. These tools were selected based on their distinctive functionalities: ChatGPT for content generation, Diffit for text simplification, and Brisk for creating multimedia presentations and teaching aids. Using a qualitative multiple case study approach, data were collected from twelve primary and junior high school ELT teachers, setting through reflective journals, focus group discussions, and document analysis. The findings of this study showed that although GAI offered strengths such as fostering creativity, enhancing accessibility, and engaging students, the tools also have some limitations in terms of content inaccuracy, oversimplification, and lack of contextual adaptability. Therefore, teacher intervention is required in its implementation. In this study, teachers used reflection-in-action to make real-time adjustments, reflection-on-action to refine the integration strategies, and collaborative reflection to exchange best practices. Additionally, findings highlight teacher agency importance in leveraging AI for lesson planning and differentiated instruction. It further highlights the need for professional development in AI literacy to equip educators with skills to evaluate and adapt AI-generated content critically. This research contributes to the growing discourse on AI in Education, demonstrating how generative AI can function as a teaching aid rather than a replacement for pedagogical experts.